Database Performance Tuning Methods for Manufacturing Execution System - Khushairi, N. M; Nurul A., Emran; Yusof, M. M. M. (2013)
In manufacturing industry where data are produced and shared every day, data volumes could be large enough for the database performance to become an issue. Manufacturing Execution System (MES) is such a system that cannot tolerate with poor database performance as the system relies heavily on real-time reporting that requires instance query responses. Manufacturing products’ quality and production targets can be affected as the result of delayed queries. Therefore, the need to maintain the acceptable level of database performance in this domain is crucial. One task in maintaining database performance is identification and diagnosis of the root causes that may cause delayed queries. Poor query design has been identified as one major cause of delayed queries that affect real-time reporting. Nevertheless, as various methods available to deal with poor query design, it is important for a database administrator to decide the method or combination of methods that work best. In this paper, we present a case study on the methods used by a real manufacturing industry company called as Silterra and the methods proposed in the literature that deal with poor query design. For each method, we elicit its strength and weaknesses and analyse the practical implementation of it.